2019
DOI: 10.1088/1361-6471/ab5374
|View full text |Cite
|
Sign up to set email alerts
|

Possible antimagnetic rotational band in 127Xe

Abstract: Excited states of 127Xe were populated in the 122Sn(9Be, 4nγ) fusion-evaporation reaction at a beam energy of 48 MeV. A sequence of ΔI = 2 γ-transitions has been observed above the Iπ = 19/2+ state at 2307 keV. Spin and parity of the states belonging to this band have been assigned firmly. The dynamic moment of inertia of this band is found to be low and almost constant as a function of angular momentum. Observed experimental features along with the results of theoretical semiclassical model calculation sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Recently, in the case of 127 Xe, it has been shown that this band originated due to the simultaneous excitation of wobbling and γ-phonons [27]. Apart from these negative parity bands, a number of positive parity bands are also observed in this nucleus [53][54][55][56].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, in the case of 127 Xe, it has been shown that this band originated due to the simultaneous excitation of wobbling and γ-phonons [27]. Apart from these negative parity bands, a number of positive parity bands are also observed in this nucleus [53][54][55][56].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, numerical calculations within the framework of a geometric model were devised to study the competition between the shears mechanism and core rotation [10,11,27,30,63]. In this model, high-j neutrons and high-j proton holes are represented by classical angular momentum vectors (blades).…”
Section: H Intrmentioning
confidence: 99%
“…The classical PRM, initially developed by Macchiavelli et al for magnetic rotation [30,64], was extended by Sugawara and Roy et al for AMR bands [10,11,27]. During the last two decades, the characteristic properties of AMR bands have been reasonably described with the help of the classical PRM in many nuclei, such as 105,106,107,108,109,110,111 Cd [8−11], 100,101,104 Pd [3,15,16], and 127 Xe [28].…”
Section: H Intrmentioning
confidence: 99%
“…In the A ≈ 130 region, a number of γ-bands were reported in both even-A, Z and odd-A, Z nuclei. Both even and odd spin sequences of the γ-bands were observed in even-A, Z [122][123][124][125][126][127][128] Xe [25][26][27][28], [124][125][126][127][128][129][130] Ba [29][30][31][32], [130][131][132][133][134][135][136] Ce [33][34][35][36] nuclei. Band structures of the odd-A, Z nuclei in this mass region were generally interpreted in terms of coupling between an odd-proton and the states of the corresponding even-A, Z core.…”
Section: Introductionmentioning
confidence: 99%
“…Structures of the Te nuclei, having two protons outside the Z = 50 shell closure, are quite debatable. The low lying yrast states in [120][121][122][123][124][125][126][127][128][129][130] Te nuclei show vibrational-like nature, having nearly equal energy spacing [47][48][49][50][51]. In contrast to this, the measured reduced transition probabilities and predictions of large-scale shell model (LSSM), shell model Monte Carlo (SMMC) and total Routhian surface (TRS) calculations supported the γ-soft (asymmetric-rotor) nature of these nuclei [52][53][54].…”
Section: Introductionmentioning
confidence: 99%